HISTORICAL STAGES IN THE DEVELOPMENT OF UZBEK FOLK ART - Madrimov Bahrom Khudoynazarovich (Scholar Express Journal, 2021)
The earliest examples of verbal art began to appear with the advent of human speech. Conditions of that period in its existence. People's life and work experience, worldview, customs and rituals play a decisive role. First of all, prose works appeared. They are extremely simple. It only consists of various references and event descriptions. That is, a labour assistant. Refreshing spirit. Fairy tales and legends were created, generated by fantasy, samples of songs depicting the labour process arose.
Keywords: pedagogy; education; technology; method; innovation; learning process